2008
DOI: 10.1161/hypertensionaha.107.104463
|View full text |Cite
|
Sign up to set email alerts
|

A Single Nucleotide Polymorphism in the CYP4F2 but not CYP4A11 Gene Is Associated With Increased 20-HETE Excretion and Blood Pressure

Abstract: Abstract-Arachidonic acid is a major fatty acid that can be metabolized by the cytochrome P450 enzyme to a number of bioactive eicosanoids. A major metabolite of this oxidation is 20-hydroxyeicosatetraenoic acid, which acts as a potent vasoconstrictor. However, in the kidney, its vasoconstrictor actions can be offset by its natriuretic properties. A guanine-to-adenine polymorphism in the CYP4F2 gene was associated with a reduction in 20-hydroxyeicosatetraenoic acid production in vitro. A thymidine-to-cytosine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
141
3
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(155 citation statements)
references
References 23 publications
10
141
3
1
Order By: Relevance
“…Apart from the rs9333025 variant, there were no significant differences in association with IS identified for other variants using a singlelocus analytical approach. These results were consistent with those of some previous studies 29,34,35) and in contrast to some others 20,22,[25][26][27][28][36][37][38] . For instance, Gschwendtner et al have reported that genetic variations in the EPHX2 gene are associated with IS risk, an association that has been described as predominantly mediated by large-vessel disease 36) .…”
Section: Logistic Regression Analysissupporting
confidence: 94%
See 2 more Smart Citations
“…Apart from the rs9333025 variant, there were no significant differences in association with IS identified for other variants using a singlelocus analytical approach. These results were consistent with those of some previous studies 29,34,35) and in contrast to some others 20,22,[25][26][27][28][36][37][38] . For instance, Gschwendtner et al have reported that genetic variations in the EPHX2 gene are associated with IS risk, an association that has been described as predominantly mediated by large-vessel disease 36) .…”
Section: Logistic Regression Analysissupporting
confidence: 94%
“…Similarly, Zhang et al have reported that the EPHX2 860A allele is associated with a significantly reduced risk of IS 37) . In addition, Ward et al have reported that a single polymorphism in the CYP4F2 gene is associated with increased 20-HETE 38) . Some studies also have reported that CYP4F2 polymorphisms are associated with IS risk [25][26][27][28] .…”
Section: Logistic Regression Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…25,26 Interpretation of our results is complicated by the discrepant in vitro/in vivo findings on the effect of CYP4F3*3 on 20-HETE levels, which despite decreased activity in vitro have shown increased 20-HETE concentrations in the urine of patients. 16,27 With respect to CYP4A11, our genetic analysis showed that patients with the variant g.4207G-allele located in the promoter region of CYP4A11 showed 43% lower mean 20-HETE CSF levels. In silico models predicted that this SNP will lower CYP4A11 transcriptional activity.…”
Section: Discussionmentioning
confidence: 89%
“…Many candidate genes have been reported to be involved in essential hypertension susceptibility, including TSC, NEDD4L (Luo et al, 2009), CYP4F2 (Ward et al, 2008), EMILIN 1 (Shimodaira et al, 2010), ATP2B1 (Tabara et al, 2010), apelin-AGTRL1 system (Niu et al, 2010), and so on. Several studies suggest that TSC plays a major role in sodium and chloride re-absorption in the distal convoluted tubule, accounting for a significant proportion of the total renal sodium re-absorption (Plotkin et al, 1996;Matsuo et al, 2004).…”
Section: Discussionmentioning
confidence: 99%